2022
DOI: 10.2196/36962
|View full text |Cite
|
Sign up to set email alerts
|

The Sociodemographic Digital Divide in Mobile Health App Use Among Clients at Outpatient Departments in Inner Mongolia, China: Cross-sectional Survey Study

Abstract: Background Mobile health (mHealth) apps have become part of the infrastructure for access to health care in hospitals, especially during the COVID-19 pandemic. However, little is known about the effects of sociodemographic characteristics on the digital divide regarding the use of hospital-based mHealth apps and their benefits to patients and caregivers. Objective The aim of this study was to document the cascade of potential influences from digital acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Age is also an important predictor of app use-in general, older people do not use mHealth services [46]. Our results overall replicated this tendency, which may point to digital divides among an older population.…”
Section: Principal Findingssupporting
confidence: 77%
“…Age is also an important predictor of app use-in general, older people do not use mHealth services [46]. Our results overall replicated this tendency, which may point to digital divides among an older population.…”
Section: Principal Findingssupporting
confidence: 77%
“…In general, women are dominant users of healthcare apps (for diet, nutrition, and self-care), but fitness apps are an exception as they are more preferred by men [46]. Older people typically avoid new technology and mHealth services [49]. In contrast, our results indicated that older users were more likely to continue using apps.…”
Section: Demographic Characteristics Of Continued Vs Discontinued Usersmentioning
confidence: 65%
“…Despite these advances in methodology, the datasets available initially were only applicable to the state of Indiana, making its application limited. Addressing these shortcomings, our group developed the Digital Inequity Index (DII) that utilized similar methodologies and data sources of the Digital Divide Index while expanding the coverage to the entirety of the United States at the county level [50 ▪ ].While many recent works on digital inequity have encompassed literature reviews and small-scaled implementation studies on diseases such as breast cancer, brain tumors, and COVID-19 [51 ▪▪ ,52 ▪▪ ,53–57], modern large-data analyses on digital inequity have only been performed on cancers of the esophagus and gastrointestinal system by our group [50 ▪ ]. In short, this study observed that, after adjusting for the impact of traditional SDoH, such as education level, income, disability status, and others, poorer digital resource access contributed to upwards of 20% differences in postoperative surveillance and 16% differences in survival time for patients diagnosed with esophageal and other types of gastrointestinal malignancies.…”
Section: Text Of Reviewmentioning
confidence: 99%